A review of salivary composition changes induced by fasting and its impact on health - Nurul Fadhilah Kamalul Aripin; N. Idayu Zahid; Mohd Aizat Abdul Rahim; Hashim Yaacob; Parvez I. Haris; Zubaidah Haji Abd. Rahim; Rauzah Hashim (Food Science and Human Wellness)
Human saliva is an indispensable fluid that maintains a healthy oral cavity which otherwise can lead to oral diseases (dental caries and periodontitis). In addition, salivary metabolites and microbiome profile provide early detection of systemic diseases such as cancer and obesity. Salivary diagnostic has gained popularity due to its non-invasive sampling technique. Fasting (abstinence from food or drink or both) research for weight loss and improve health is common, but studies using fasting saliva are scarce. Some metabolites in fasting saliva have been reported with interesting results, which can be enhanced by considering different confounding factors. For example, fasting saliva contains higher salivary nitrite, which is related to nitric oxide (NO). NO is a vasodilator supporting the healthy function of endothelial cells and its deficiency is connected to many diseases. The timely supply of NO through exogenous and endogenous means is highlighted and the potential advantage of fasting salivary composition changes in relation to COVID-19 infection is speculated. This review aims to provide a general discussion on the salivary composition, properties, and functions of the whole saliva, including the health benefits of fasting.